Leaching behaviors of heavy metals on petroleum sludge waste treatment by using solidification/stabilization (s/s) method with palm oil fuel ash as partial cement replacement - Murshid, Noorafizah (2018)
In Malaysia, petroleum is the most important source of energy which also producing hazardous waste called sludge. Petroleum sludge is referring to the waste containing mixtures of high concentration of hydrocarbons and accumulated heavy metals which being recognized as a hazardous waste. Without improper disposal or insufficient treatment, it can pose serious threats to the environment and human health. To solve these problems, there is a method has been developed for the treatment of petroleum sludge namely the solidification/stabilization (S/S) method. S/S method mainly based on the encapsulation of the pollutants within matrices using the cement. Tremendous research has been carried out using the ash from different sources in the S/S method as environmentally-friendly solutions. It replaces cement with a high pozzolonic characteristics binder that could encapsulate the pollutants better. Therefore, this study is an attempt to treat the Malaysian petroleum sludge (PS) by the incorporation of different percentage of palm oil fuel ash (POFA) to replace ordinary portland cement (OPC) in S/S method. The leachibility of the samples was determined by Synthetic Precipitation Leaching Procedure (SPLP), Toxicity Characteristics Leaching Procedure (TCLP) and Static Leaching Test (SLT). The results were compared with United States Environmental Protection Agency (USEPA) standards. The heavy metals in PS, POFA and OPC were determined using X-ray Fluorescence (XRF) meanwhile dissolved heavy metals using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Addition test such as compressive strength test, density test and water absorption test were conducted on S/S matrices. The recommended percentage of POFA incorporation was 10% into 30% of PS with leachibility complies to USEPA standard except for Ni and Cr. It performed better in physical and mechanical properties. SPLP leaching test results for PS mix OPC showed at 28th day curing, the highest leaching was 15.2 mg/L (Cr; 40% PS) meanwhile for PS mix OPC and POFA was 14.2 mg/L (Cr; 30% PS). The results showed that the full utilization of S/S matrices obtained the highest compressive strength up to 30.1 MPa. Meanwhile, the lowest 0.71 MPa was above the limit of 0.35 MPa. The long term leachibility results also showed that all findings were below the USEPA standard. On 95th day curing was the recommended time after treating the S/S matrices to be disposed into landfill. Therefore, POFA can be an alternative low cost material that supports an environmentally friendly disposal method and also enhances the petroleum sludge treatment performance.